Pelatihan Kewirausahaan Sosial Berkelanjutan: Membangun Kesadaran Dampak Sosial di Kalangan Mahasiswa TGBC, Thailand - Nindria Untarini; Widyastuti Widyastuti; Agus Frianto; Monika Tiarawati (Universitas Negeri Surabaya, 2026)
Sustainable social entrepreneurship integrates entrepreneurial strategies with a commitment to social and environmental objectives. This study identifies two major issues based on interviews with partners at the Thai Global Business Administration Technological College (TGBC), Thailand. Although TGBC students demonstrate strong entrepreneurial potential and innovative ideas, their understanding of sustainable social entrepreneurship and experience in implementing sustainable social business practices remain limited. To address these gaps, an integrated training program was designed to enhance conceptual understanding and practical business skills through four stages: preparation, implementation, monitoring, and evaluation. Participants reported high satisfaction with the program’s facilities—including training venues, equipment quality, internet access, cleanliness, and learning materials—and with the training process, particularly the clarity of materials, expertise of facilitators, adequacy of training duration, and responsiveness of organizers (92%). Post-training evaluations indicated improved comprehension of social entrepreneurship, competence in applying the Sustainability Business Model Canvas (SBMC), and increased confidence and motivation (92%). Furthermore, most participants perceived the program as beneficial for both career and academic development (96.4%). These findings highlight the importance of structured, experiential learning in fostering sustainable social entrepreneurship among students. Keywords: Social entrepreneurship, sustainable entrepreneurship, Sustainability Business Model Canvas (SBMC), training